Technical Efficiency of Turmeric Production in Sri Lanka: A Stochastic Frontier Approach - Perera, M.I.D.; Dishanka, S. (Colombo Economic Journal, 2024)
While acknowledging the substantial contribution of Sri Lanka’s agricultural sector to the economy's total agricultural output, experts have found that spices are not produced at total capacity. Among agricultural export items, turmeric is still not fully exploiting the country’s agricultural resources. Due to input-related issues, this sector is affected by several deficiencies. Accordingly, this study has been designed to estimate the technical efficiency of turmeric production and determinants of technical inefficiency in Sri Lanka using cross-sectional survey data collected from turmeric producers from six districts in Sri Lanka. The sample was decided using a multistage random sampling approach. The data was analyzed using maximum likelihood estimates of the stochastic frontier production function and technical inefficiency model. The results revealed that the average technical efficiency of the turmeric sector was 74%, with a 26% margin for improvement through better use of available resources and technology. The results of the Cobb-Douglas production function and stochastic frontier production function showed that the size of the land and the number of seeds were the major inputs that determine the production. The results of the inefficiency model revealed that family size and farmer’s experience have significant effect on technical inefficiency.
Keywords: Inefficiency; Resource Optimization; Sri Lanka; Stochastic Frontier Approach; Technical Efficiency; Turmeric Production